Theology and botho/ubuntu in dialogue towards South African social cohesion - Resane, Kelebogile T. (HTS teologiese studies, 2022)
South Africa is one of the most unequal societies in the world. This article is a literature study on the role of theology and the African philosophy of botho or ubuntu trying to address this social inequality. It is this situation that has led to poor (if not the absence of) cohesion in society. It shows how theology through its constructive nature has for years shifted from dogmatism to interdisciplinary dialogue with other sciences and philosophies in order to arrive at facts that are helpful to building harmonious societies. Dialogue is a vehicle that makes this interaction possible. It is pointed out that dogmas, creeds, symbolics, apologetics, etc., all emanated from dialogical deliberations. Botho as life practice of humanity to others is a philosophy that emphasises togetherness or communality. It is a philosophy that puts an individual at the centre of a community. No individual can be contextually rooted without other human beings. It is the people in context that give individuals the meaning and the essence of life. The goal of this dialogue is social cohesion, which is defined as strong relationships enhanced by a sense of solidarity amongst members of a community. It is when botho is socially situated, resulting in theology constructed through dialogue towards desired social cohesion, in order to address the cosmic imbalances that threaten humans’ quality of life. It can be presented in a formula: theology + botho or ubuntu = cohesive society.Contribution: This article contributes towards the importance of dialogue between theology and the African philosophy of botho. The dialogue leads to social cohesion which is needed for harmonious co-existence in unequal society of South Africa.